The Short-Term Effects of Lying, Sitting and Standing on Energy Expenditure in Women - POPP, COLLIN J. (Int J Exerc Sci, 2018)
The deleterious health effects of too much sitting have been associated with an increased risk for overweight and obesity. Replacing sitting with standing is the proposed intervention to increase daily energy expenditure (EE). The purpose of this study was to determine the short-term effects of lying, sitting, and standing postures on EE, and determine the magnitude of the effect each posture has on EE using indirect calorimetry (IC). Twenty-eight healthy females performed three separate positions (lying, sitting, standing) in random order. Inspired and expired gases were collected for 45-minutes (15 minutes for each position) using breath-by-breath indirect calorimetry. Oxygen consumption (VO(2)) and carbon dioxide production (VCO(2)) were measured to estimate EE. Statistical analyses used repeat measures ANOVA to analyze all variables and post hoc t-tests. Based on the ANOVA the individual, time period and order term did not result in a statistically significant difference. Lying EE and sitting EE were not different from each other (P = 0.56). However, standing EE (kcal/min) was 9.0 % greater than lying EE (kcal/min) (P = 0.003), and 7.1% greater than sitting EE (kcal/min) (P = 0.02). The energetic cost of standing was higher compared to lying and sitting. While this is statistically significant, the magnitude of the effect of standing when compared to sitting was small (Cohen’s d = 0.31). Short-term standing does not offer an energetic advantage when compared to sitting.